2012
DOI: 10.1186/1471-244x-12-199
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of antipsychotic drugs on autonomic nervous system activity in schizophrenia

Abstract: BackgroundAntipsychotic drugs are considered a trigger factor for autonomic dysregulation, which has been shown to predict potentially fatal arrhythmias in schizophrenia. However, the dose-dependent effect of antipsychotic drugs and other psychotropic drugs on autonomic nervous system (ANS) activity remain unclear. The purpose of this study was to investigate the dose-dependent effect of antipsychotic drugs and other clinical factors on ANS activity in an adequate sample size of patients with schizophrenia.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 36 publications
0
38
1
1
Order By: Relevance
“…In fact the oral benzodiazepines, used for the treatment of insomnia and anxiety in community-dwelling subjects, unlike the intravenous ones [171], [172] have mostly been reported to have no effect on HRV [165], [167], [169], with some exception [166], [168]. Moreover, a recent and larger study in patients with schizophrenia [154], making no distinction between routes of administration, demonstrated that daily benzodiazepine dose was not associated with frequency-domain measures of HRV.…”
Section: Discussionmentioning
confidence: 99%
“…In fact the oral benzodiazepines, used for the treatment of insomnia and anxiety in community-dwelling subjects, unlike the intravenous ones [171], [172] have mostly been reported to have no effect on HRV [165], [167], [169], with some exception [166], [168]. Moreover, a recent and larger study in patients with schizophrenia [154], making no distinction between routes of administration, demonstrated that daily benzodiazepine dose was not associated with frequency-domain measures of HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, parasympathetic nervous system (PNS) activity was reduced in patients with schizophrenia [2,3]. Our research has shown that high doses of antipsychotic medication can affect ANS function in patients with schizophrenia [7], and previous studies have also demonstrated that antipsychotic medication affects ANS activity in such patients [8,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 88%
“…To study the dose-dependent effects of antipsychotic drugs, we categorized the patients according to their daily dose of antipsychotics as high-dose antipsychotic drug group (HG) patients and low-dose antipsychotic drug (LG) patients receiving the antipsychotic chlorpromazine (CP) equivalent daily dose ≄1,000 or <1,000 mg, respectively. This categorization is based on our previous research which showed that high doses of antipsychotic medication (CP equivalent daily dose ≄1,000 mg) affected ANS function in patients with schizophrenia [7]. The CP equivalent dose is expressed as “mg CP.” A dose comparability table prepared by Inada and Inagaki [26] to convert the doses of various antipsychotics to CP is routinely adopted in Japan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SampEn and/or alpha had a higher correlation with subscales and SE total compared to the linear parameters, suggesting that non‐linear HRV properties better reflected SE. A recent study suggested that central autonomic activity might be a biomarker for SE of antipsychotic drugs rather than severity of schizophrenia . Post‐hoc partial correlation analysis also confirmed that SampEn may be directly linked with subjective discomfort independent of psychopathology.…”
Section: Discussionmentioning
confidence: 68%